Hubungan Sumber Informasi, Asupan Gizi, dan Dukungan Keluarga Terhadap Tumbuh Kembang Bayi 0-12 Bulan di Puskesmas Maripari Tahun 2023 - Winarti, Winda; Hayatullah, Madinah Munawaroh; Kusumastuti, Istiana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Growth and development can be influenced by good nutritional intake, parenting patterns, sources of information and also family support, most of which nutritional intake has a very significant effect on the growth and development of babies 0-12 months. The aim of this research is to determine the relationship between sources of information, nutritional intake and family support on the growth and development of babies 0-12 months at the Maripari Community Health Center in 2023 using quantitative research methods, and the research design used is analytical descriptive with a sample size of 54 respondents. The results of the Chie Square test, there is a significant relationship between the source of information on the growth and development of babies 0-12 months with a p value of 0.027, there is a significant relationship between nutritional intake and the growth and development of babies 0-12 months with a p value of 0.0000, and there is a There is a significant relationship between family support and the growth and development of babies 0-12 months with a p value of 0.014. Conclusion: Nutritional intake has the greatest influence on the growth and development of babies 0-12 months, it is recommended for mothers or respondents to be smarter in processing food or give food to the baby.